Türk Vergi Sisteminde Vergi İadeleri ve Çeşitli Yönlerden Değerlendirilmesi - (:unkn) unknown (My University, 2016)
Ülkemizde yapılan vergi iadesi her yıl artan bir seyir izlemekte olup vergi iadesi iktisadi, sosyal, mali, vergi tekniği ve diplomatik nedenlerden dolayı yapılmaktadır. Ülkemizdeki vergi iade sistemiyle Avrupa Birliğindeki vergi iadesi sistemi arasında ciddi farklar mevcuttur. Bununla birlikte vergi iadesi 1982 Anayasasında yer alan temel hak ve hürriyetlerle de yakından ilgilidir

The tax refunds made in our country have an increasing trend, and they are made due to the tax technique as well as economic, social, financial, and diplomatic reasons. There are significant differences between the tax refund system in our country and the tax refund system in the European Union. In addition, tax refund is also closely connected to the basic rights and freedoms covered in the 1982 Constitution
TAX RETURNS IN THE TURKISH TAX SYSTEM
Keywords: İşletme Finans; İktisat; Tarih; Beşeri Bilimler; İşletme